A Case Report of Thoraco-Omphalopagus Conjoined Twins: The Downfall of the Separated Hearts - Safira, Siti Anissa; Chalid, Maisuri T; Madya, Fatmawati (Indonesian Journal of Obstetrics & Gynecology Science, 2024)
Introduction: Thoraco-omphalopagus conjoined twins are a rare occurrence of monozygotic pregnancy that involves fusion of the anterior thorax and abdomen. This type presents a variety of cardiac anomalies, which contribute to its generally unfavorable prognosis.Case Presentation: A 32-year-old multigravida with Gravida 6, Para 4, and Abortus 1 was referred at 28 weeks of gestation. Ultrasonography revealed thoracoomphalopagus-conjoined twins in which the fetuses joined ventrally. Prenatal MRI revealed the sharing of a single liver, omentum, and diaphragm. Partial fusion was observed in the sternal bone, pericardium, and anterior wall of the hearts, but with separated heart chambers and unsynchronized heartbeats. Classical cesarean section was performed at 38 weeks of gestational age. Histopathology revealed a single placenta with one umbilical cord, suggesting monochorionic– monoamniotic pregnancy. Healthy female babies were born with a combined weight of 5400 g. Post-delivery echocardiography revealed a cardiac anomaly characterized by malposition of the great arteries in a twin. After 13 h of close monitoring in the NICU, the twins died due to cardiac complications.Conclusion: The management of pregnancy involving thoraco-omphalopagus conjoined twins requires a comprehensive and multi-disciplinary approach aiming to provide holistic care, addressing complex medical risks, and ethical dilemmas associatedwith these twins.Laporan Kasus Mengenai Kembar Siam Torako-Omfalopagus: Prognosis Buruk pada Jantung yang TerpisahAbstrakPendahuluan: Kembar siam thoraco-omphalopagus adalah kejadian langka pada kehamilan monozigot yang melibatkan penyatuan antara toraks dan abdomen anterior. Tipe ini diketahui dapat disertai adanya kelainan jantung yang berkontribusi terhadap prognosis yang umumnya kurang baik.Presentasi Kasus: Multigravida berusia 32 tahun dengan Gravida 6, Para 4, Abortus 1, dirujuk pada usia kehamilan 28 minggu. Ultrasonografi menunjukkan kembar siam torako-omfalopagus di mana janin menyatu secara ventral. MRI prenatal memperlihatkan adanya fusi organ hati, omentum dan diafragma. Di sisi lain, fusi parsial diamati pada sternum, perikardium, dan dinding anterior jantung, dengan ruang jantung terpisah dan detak jantung yang tidak bersifat sinkron.Seksio sesarea klasik dilakukan pada usia kehamilan 38 minggu. Histopatologi menunjukkan plasenta tunggal dengan satu tali pusat sugestif kehamilan monokorionik-monoamniotik. Dua bayi perempuan sehat lahir dengan berat kombinasi 5.400 gram. Ekokardiografi pascasalin menunjukkan adanya anomali jantung berupa malposisi arteri besar pada salah satu bayi. Setelah 13 jam observasi ketat di NICU, kedua bayi kembar meninggal akibat komplikasi jantung.Kesimpulan: Penatalaksanaan kehamilan kembar siam thoraco-omphalopagus memerlukan pendekatan komprehensif dan multidisiplin yang bertujuan untuk memberikan perawatan holistik, mengatasi risiko medis, dan dilema etika yang terkait.Kata kunci: Kembar Siam; Kembar Monozigotik; Thoraco-omphalopagus